“Woman is the Nigger of the World”. An approach to the countercultural path Lennon-Ono - Molinari, Tirso (2018)
An approach is intended from interactionist sociology, as well as cognitive linguistics, to J. Lennon and Y. Ono’s both aesthetically-popular and political countercultural position particularities, based on the claim that combines feminism and the struggle against racism at the same time in a metaphorical way, and in the early 70s, it is anticipated to expert views from the social sciences, mainly Latin American ones, that systematise approaches, from the early 90s, where racism and ethnicity with patriarchy are correlated from ethnic-critical theoretical perspectives basically linked to postcolonial studies, the so-called coloniality of power and researches into subalternity.